2018
DOI: 10.1111/cdoe.12363
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and anger of homeless people coping with dental care

Abstract: Homeless people have difficulty coping with dental care. They believe that dentistry is frightening, humiliating and expensive, and governments are neither sympathetic to their disability nor willing to provide helpful information about community dental clinics or sufficient dental benefits for their needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
(48 reference statements)
1
18
0
Order By: Relevance
“…It is possible that the participants from this study did not have a dental visit within the last year due to these difficulties and competing priorities. The most significant predictor in multivariate analysis was anxiety, a well‐known factor preventing people from seeking dental care regardless of age, race, or socio‐economic status .…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the participants from this study did not have a dental visit within the last year due to these difficulties and competing priorities. The most significant predictor in multivariate analysis was anxiety, a well‐known factor preventing people from seeking dental care regardless of age, race, or socio‐economic status .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported unmet dental treatment needs amongst PLHIV . Hence, it is believed that low levels of dental service utilization among PLHIV exist due to accessibility, affordability and other compounding factors, similarly to other vulnerable groups, including pregnant women, indigenous people, and the homeless . Various psychosocial disparities such as lack of financial affordability, not having dental insurance and experiencing discrimination by dental professionals leads to higher unmet dental treatment needs of PLHIV .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, postintervention findings from the qualitative survey also reported students’ perception of having more positive attitudes and empathy towards patients, especially the underprivileged. Such attitudes are important in removing discrimination and barriers to professional care, as reported previously by some groups of underserved population, including those with infectious diseases and social deprivation 24,25 . Besides this, having positive attitudes is integral to improving access to dental services that have been associated with dentists’ lack of professionalism, particularly in managing patients with special health care needs 26 …”
Section: Discussionmentioning
confidence: 88%
“…Such attitudes are important in removing discrimination and barriers to professional care, as reported previously by some groups of underserved population, including those with infectious diseases and social deprivation. 24,25 Besides this, having positive attitudes is integral to improving access to dental services that have been associated with dentists' lack of professionalism, particularly in managing patients with special health care needs. 26 Students' appreciation towards exposure to various scenarios depicted in the photographs, as well as how they are linked to clinical care, together indicate an opportunity for teaching and learning that supports the concept of comprehensive patient management.…”
Section: Discussionmentioning
confidence: 99%